Answer:
(- 4, 1 )
Step-by-step explanation:
Given the 2 equations
y = x + 5 → (1)
x - 5y = - 9 → (2)
Substitute y = x + 5 into (2)
x - 5(x + 5) = - 9 ← distribute and simplify left side
x - 5x - 25 = - 9
- 4x - 25 = - 9 ( add 25 to both sides )
- 4x = 16 ( divide both sides by - 4 )
x = - 4
Substitute x = - 4 into either of the 2 equations and evaluate for y
Substituting into (1)
y = - 4 + 5 = 1
Solution is (- 4, 1 )
The answer is b 16 caz I got it on the website www.asknumbers.com
Answer: (1, -5)
x = 1
y = -5
*Hope this helps, enjoy the rest of your day! ♥️*
Answer:
7.35
Step-by-step explanation:
5 pounds -> 5.25
1 pound -> 1.05
7 pounds-> 7.35
Answer:
10
Step-by-step explanation:
10x2+10
=10(2x+1)